2001
DOI: 10.1002/1097-0142(20010601)91:11<2165::aid-cncr1245>3.3.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Only pathologic complete response to neoadjuvant chemotherapy improves significantly the long term survival of patients with resectable esophageal squamous cell carcinoma

Abstract: Patients with resectable esophageal carcinoma who underwent preoperative chemotherapy and obtained a pathologic complete response had a significantly improved long term survival. Major efforts should be undertaken to identify patients before neoadjuvant treatments who are likely to respond.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
150
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(158 citation statements)
references
References 15 publications
7
150
0
1
Order By: Relevance
“…Some authors [8] reported up to 16% of treatment-related deaths with the same combination, even using chemotherapy alone. In a randomized study in operable patients [3], using preoperative CT alone, we were able to deliver 68% of three planned cycles of FU/cisplatin. In a similar study, Kelsen et al [24] delivered 71% of the planned CT preoperatively, and 38% postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors [8] reported up to 16% of treatment-related deaths with the same combination, even using chemotherapy alone. In a randomized study in operable patients [3], using preoperative CT alone, we were able to deliver 68% of three planned cycles of FU/cisplatin. In a similar study, Kelsen et al [24] delivered 71% of the planned CT preoperatively, and 38% postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…The response rate reported with PF ranged from 35 to 40% (De Besi et al, 1986;Bleiberg et al, 1997;Ancona et al, 2001), whereas the 2-year survival rates of patients with locally advanced oesophageal cancer ranged from 8 to 55%, with a mean 27%. A better prognosis with chemoradiotherapy/chemotherapy (al-Sarraf et al, 1997;Stuschke et al, 2000;Kodaira et al, 2003;Polee et al, 2003) has been reported, but these series also included patients with potentially resectable carcinomas.…”
mentioning
confidence: 99%
“…The majority of studies on combined therapy showed longer survival for patients achieving a pathologic complete response (pCR), which can be obtained in 12 -40% of patients treated with PF combined therapy Ancona et al, 2001). Patients with a less advanced stage are more likely to achieve a pCR than those with a more advanced disease (Rohatgi et al, 2005).…”
mentioning
confidence: 99%
“…These studies have indicated a complete response in 20 -40% of patients preoperatively treated with combined radiotherapy and chemotherapy (Ilson, 2004). However, with regard to survival, the benefit of combined neoadjuvant treatment modalities has only been confirmed unequivocally in the subset of patients who have a complete response at histopathological examination (Lerut et al, 1999;Ancona et al, 2001;Brücher et al, 2004). Finding parameters that might help identify those patients capable of benefiting from multimodal treatment modalities before the start of therapy would therefore be of considerable interest (Lerut et al, 1999;Ilson, 2004).…”
mentioning
confidence: 99%